Materials and methods used for adhesive remnant removal and polishing of enamel after orthodontic treatment: a review - Kandikatla, Pradeep; Polineti, Priyanka; Ushasree, R; Chiluvuri, Pavan Kumar (International Journal of Dental Materials, 2022)
Brackets are generally debonded and the remaining adhesive is removed at the end of the orthodontic treatment. There are different methods for adhesive removal of which few methods have a chance of damaging enamel and roughening the tooth surface which can lead to plaque accumulation, discolouration, and aesthetic problems. Enamel polishing after debonding is one strategy to decrease such consequences. Several enamel cleaning and polishing methods include Sof-Lex discs, TC burs, ultrasonic tools, hand instruments, rubbers, composite burs, Arkansas stones, green stones, diamond burs, steel burs and lasers. Each method has some advantages and some lacunae. To be precise soflex discs and TC burs have less damage on enamel than other methods, i.e., Arkansas stone and greenstone. This article is a review of available different enamel cleaning and polishing methods after debonding, their advantages and disadvantages.